Customer Satisfaction in Service Companies: the Case of the Restaurant Industry (2011)
The services industry has experienced a change during the past few years to become an important line of business in the economy of Latin American countries. This is due not only to the performance of industries in this sector, but also to the fact that all sectors in these economies began to add different services to their products aiming at increasing their product value and setting themselves apart from their competitors. When it comes to loyalty to and preference for restaurant services, customer satisfaction makes a difference. It is something that the industry requires from businesses for them to be successful. It goes without saying that offering an excellent quality product is also essential to be able to stand out in this industry. The purpose of this research study is to establish the determining factors of consumer satisfaction in the restaurant industry and to provide them with a tool that allows identifying the most important factors for achieving customer satisfaction.